Does Citizen Participation Improve Local Planning? An Empirical Analysis of Stakeholders' Perceptions in Nepal. (December 2016) - Pandeya, Ganesh Prasad; Shrestha, Shree Krishna
Using a qualitative approach, based on extensive fieldwork and surveys, this article examines how participatory institutions in Nepal perform and affect local planning. The evidence points to mixed outcomes: citizen participation can improve local planning, especially with regard to achieving planning efficacy and equity; and at the same time, it sometimes yields no such effects or may produce negative effects including raising expectations, skewing priorities and producing faulty compartmentalization, besides adding to administrative complexities. This is because the anticipated benefits of citizen participation are strongly embedded in local, socio-political realities such as the degree of power exercised by the local elites, mainly politicians, a collusive nexus among them, prior history of citizen mobilization and empowerment and the degree to which citizens and civil society organizations are able to exercise their agency to countervail those forces.